Distribución en planta en una fábrica dedicada a la obtención de hilo natural a partir de la fibra de la hoja de piña. (Puerto Rico, Meta). (2020)
The leaves of the pineapple plant are generally thorny, placed in a spiral shape, although depending on the variety they can be smooth, reaching a final length between 30 and 120 cm long. Its interior is composed of fibrous filaments that are fully removable and usable. The country of the Philippines is the main pioneer in the extraction and transformation of this vegetable fiber into leather and textile fiber compounds. In the country of Colombia, the fiber of the pineapple leaf is not well known and is not used for any specific purpose. In the Meta department; more exactly in the municipality of Puerto Rico, pineapple cultivation has an exponential growth year after year according to reports from the Ministry of Agriculture MINAGRICULTURE, in this municipality the association Agroindustrial Fibers Natural of Ariari CORFINAT is located, which together with the Governor of the Meta are at the forefront of a new project that consists of taking advantage of the leaves of the plant that today are considered a waste in our country. The use is based on the extraction of the pineapple leaf fiber followed by a spinning transformation process that seeks to make way for a finished product aimed at the Colombian textile sector. The problem presented by the CORFINAT company is that it does not have the necessary machinery and a standardized process that guarantees the adequate extraction of the fiber. Due to this, the company cannot achieve good levels of productivity and profitability to maintain this process. The present research project, whose general objective is to formulate a redistribution in the plant to obtain natural yarn from the fiber of the pineapple leaf in the CORFINAT company, adjusted to the needs of the national market. It is done to solve the problem previously stated; By formulating a correct plant distribution, the fiber extraction and transformation process can be carried out in a more effective way, guaranteeing adequate productivity that meets the demand of the segmented market, generating profitability.